Child-adolescent emergency psychiatry: addressing false positive admissions - Isaac, Linda; Sutton, Tiphanie; Kahlon, Jasmine; Pathania, Pratima S.; Wolf, Bradley L.; Pearce, Ryan; Chan, Helen Iat Chio; Zils, Matthew J. (Frontiers in Psychiatry, 2024)
Current literature emphasizes the necessary and increasing role of the emergency department (ED) psychologist. This perspective paper will illustrate that the recent focus on an ED psychologist is necessary, but insufficient. Equally important, is an understanding of when a patient in a potential crisis does not require an ED admission, but rather an assessment that is made prior to the patient going to the ED. The essential role of an outpatient crisis team is vital in differentiating when an ED admission is indicated for a psychiatric crisis (true positive) and when an ED admission is not indicated for a psychiatric crisis (false positive). Evaluating crises prior to ED admissions accomplishes two critical healthcare objectives in a parallel process: 1) accurately assessing the proper level of care needed when a patient reports they are experiencing acute psychiatric symptoms (which may or may not necessitate emergency department level of care, and 2) reducing burden on an already over-extended ED when emergency care is not indicated. Our findings are uniquely drawn from a highly diverse youth patient population in Northern California, United States.